2012
DOI: 10.1590/s1517-86922012000200012
|View full text |Cite
|
Sign up to set email alerts
|

Respostas lactacidêmicas de ratos ao treinamento intermitente de alta intensidade

Abstract: During high-intensity intermittent muscle contractions for short periods of time there is an important involvement of glycolytic metabolism and consequent increased blood lactate concentrations. This study aimed to evaluate the blood lactate responses in Wistar rats submitted to high-intensity intermittent training (jump squat) protocol during 6 weeks, 3 sessions, 12 x/session, 60s of interval between sessions. There was significant increase of blood lactate concentrations during the acute bout of high-intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Liver gluconeogenic efficiency is determined by glucose output at the physiological concentration of a given substrate; gluconeogenic capacity is defined as the glucose output at higher (saturating) concentrations of the substrate [22]. In resting rodents, blood lactate is around 2-3 mM [17,22,23], while that recorded immediately after the pre-perfusion ML test was at the range of 4-6 mM. Although 6 mM was not tested, the glucose output at 2, 4 and 8 mM of groups T0 and T4 indicates that the resistance HIIT for 4 weeks did not change the acute liver efficiency of NEO-lac, once glucose output was similar in the two groups at these lactate concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver gluconeogenic efficiency is determined by glucose output at the physiological concentration of a given substrate; gluconeogenic capacity is defined as the glucose output at higher (saturating) concentrations of the substrate [22]. In resting rodents, blood lactate is around 2-3 mM [17,22,23], while that recorded immediately after the pre-perfusion ML test was at the range of 4-6 mM. Although 6 mM was not tested, the glucose output at 2, 4 and 8 mM of groups T0 and T4 indicates that the resistance HIIT for 4 weeks did not change the acute liver efficiency of NEO-lac, once glucose output was similar in the two groups at these lactate concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…HIIT demands that muscle energy production is complemented by the anaerobic glycolytic system, resulting in increased lactate production by the muscle [16,17]. As training progresses, blood lactate after each training session raises less and less, which was attributed to several adaptations of muscle oxidative metabolism that would diminish lactate release during the exercise sessions [10,17].…”
Section: Introductionmentioning
confidence: 99%
“…The time interval between trials was proposed suggested by the predominance of interest via the phosphagenic and recovery. (20) If the charge were not validated on the first try is increased from 4 to 6 kg in total and is performed more two attempts always interval between three to five minutes.…”
Section: Familiarisation Stagementioning
confidence: 99%
“…Quantitatively, lactate is the major gluconeogenic precursor in any physiological circumstance (Stark & Kibbey, 2014). In addition, it is notorious that exercise intensity is an important determinant of blood lactate levels, since moderate to high intensities increase lactatemia (Furlan et al, 2017;Jamnick et al, 2020;Panveloski-Costa et al, 2012). In high-intensity exercise, for instance, the considerably increased muscle demand for ATP speeds up the glycolytic conversion of glycogen/glucose to pyruvate and then to acetyl-CoA to be oxidized in the citric acid cycle.…”
Section: Introductionmentioning
confidence: 99%
“…HIIT protocols have periods of high intensity and short duration exercise interspersed by periods of low intensity or total rest (Araujo et al, 2016;Buchheit & Laursen, 2013;MacInnis & Gibala, 2017;Wang et al, 2017). These protocols can be designed for cyclic modalities (Hawley et al, 2014;MacInnis & Gibala, 2017;Wang et al, 2017) or strength (resistance) training (Araujo et al, 2016;Muller et al, 2019;Panveloski-Costa et al, 2012). Here, the latter will be referred to as HIIRT.…”
Section: Introductionmentioning
confidence: 99%